ANALISIS METODE PEMBELAJARAN AKIDAH DI MADRASAH ALIYAH NEGERI 1 BANDA ACEH - syukri syukri (Islam Futura, 2017)
This study aims at examining the various methods of teaching akidah in Madrasah Aliyah Negeri Banda Aceh 1, as well as the suitability of its implementation with RPP documentation. This research used a qualitative approach. Hence, several techniques to collect the data including interview, observation and documentation, while data analysis using Miles and Huberman model. The results of this study indicate that the various methods of teaching akidah in MAN Banda Aceh 1 were group discussion, question and answer, inquiry, lecture, working group, training and rewarding. This study also found that methods used in teaching akidah in this school, some are in line with the RPP and some are not.